Removal of boron from aqueous solution by modified cellulose - ÇAKMAKÇI, EMRAH (SPRINGER HEIDELBERG, 2022)
Cellulose is a promising alternative material as a sorbent for the removal of pollutants. The availability of hydroxyl groups on cellulose allows for the application of various modification reactions for the development of novel sorbents with different functional groups. In this work, a cellulose sorbent modified with N-methyl-glucamine was prepared and tested for the removal of boron. A batch adsorption process was used to further explore the boron sorption kinetics, isotherms, thermodynamics, mechanism, and reuse of the prepared sorbent. It was found that the optimum sorbent dose for boron removal was 0.2 g/25 mL. Moreover, the initial pH of the solution was found to affect the removal rate and was found to be >= 4. The sorption of boron reached equilibrium within 60 min. The maximum sorption capacity was calculated to be 4.7 mg B/g sorbent. The sorption process was found to be exothermic and the negative value of increment S in the range of 30-60 degrees C is related to a decrease in randomness at the solid/solution interface during the sorption of boron on the sorbent. The sorption/regeneration experiments have shown that the removal rate of the sorbent remains the same over 5 cycles.
Keywords: Boron; Cellulose; N-Methyl-glucamine; Water treatment; BORIC-ACID; WASTE-WATER; ADSORPTION; SORPTION; POLYMERS; SEAWATER; CU2+; ION